Implementasi Proyek Penguatan Profil Pelajar Pancasila dalam Meningkatkan Sikap Beriman, Bertakwa, dan Berakhlak Mulia Siswa Kelas IV Sekolah Dasar - Rusmiati, Mei Nur; Dewi, Dinie Anggraeni; Furnamasari, Yayang Ffuri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The project of strengthening the profile of Pancasila students can be a bridge in instilling students' attitudes of faith, piety, and noble character at school. This study aims to determine the implementation of the Pancasila student profile strengthening project in improving the attitude of faith, piety, and noble character of grade IV students at SDN Sukaraja 2. The method used is descriptive qualitative. Then, data collection was obtained through interviews, observations, and documentation. The results showed: The implementation of the Pancasila student profile strengthening project in improving the attitude of faith, piety, and noble character has gone well and has a positive impact; Obstacles in the implementation of the Pancasila student profile strengthening project at SDN Sukaraja 2, namely lack of understanding, inadequate facilities, and lack of communication in the implementation of the Pancasila student profile strengthening project; Solutions to overcome the obstacles that occur, namely increasing understanding of the Pancasila student profile strengthening project, improving school facilities, and improving good communication relations. These results indicate the success in the implementation of the Pancasila student profile strengthening project in improving the attitude of faith, piety, and noble character of students at SDN Sukaraja 2.